Recommendations for the Reporting of Pancreatic Specimens Containing Malignant Tumors. Issue 3 (11th January 2016) - Albores-Saavedra, Jorge; Heffess, Clara; Hruban, Ralph H.; Klimstra, David; Longnecker, Daniel
Abstract : The Association of Directors of Anatomic and Surgical Pathology has developed recommendations for the surgical pathology report for common malignant tumors. The recommendations for malignant tumors of the pancreas are reported herein.